2022
DOI: 10.1515/jwl-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Ecolinguistics for and beyond the Sustainable Development Goals

Abstract: This article considers potential impacts the study of language, including ecolinguistics, can have on important real-world issues, and how linguists and others can involve themselves in addressing these issues for a sustainable future. The article is divided into two parts. The first part provides an illustrative study in which computer tools were utilized to investigate media reporting. The study examined the relative coverage of issues of basic human needs (food, clean water, and sanitation), which are part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In that view, privileged people use privileged languages and similarly enjoy privileged access to vaccines, sanitation, clean water, and adequate food (cf. Chau et al, 2022). This is similar to Bourdieu's (1979) work on cultural capital and Sandel's (2020) work on meritocracy.…”
Section: Global Englishes Translanguaging and A Community Of Communic...mentioning
confidence: 52%
“…In that view, privileged people use privileged languages and similarly enjoy privileged access to vaccines, sanitation, clean water, and adequate food (cf. Chau et al, 2022). This is similar to Bourdieu's (1979) work on cultural capital and Sandel's (2020) work on meritocracy.…”
Section: Global Englishes Translanguaging and A Community Of Communic...mentioning
confidence: 52%
“…They also stated that ecolinguistic aspects were not really got enough attention from the Iranian English textbooks' writers or publishers. Chau et al, (2022) mentioned that topics related to environmental issues such as famine, water pollution, or sanitation were not discussed very often. Meanwhile the topic of the current pandemic, Covid-19 were frequently discussed.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the role of the UN, climate activists, and political parties in climate preservation is undeniable, and specific studies have been conducted to critically assess their climate discourse. These studies (Abdurrahman, 2023;Chau et al, 2022;Wang, Zhai, & Zhao, 2019;Yuniawan, et al, 2017) have primarily identified the following key areas in the selected discourses: appeals to all the stakeholders to take responsibility for climate awareness; devise immediate remedial actions and plans; and implement these plans seriously.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When it comes to the Saudi context, an observable dearth of studies with a perspective on ecolinguistics analysis of climate issues in media discourse emerges. Only a few studies, such as (Almaghlouth, 2022;Al-Jayyousi, 2023;Chau et al, 2022;Hameed, Jabeen & Mehar, 2022) have offered critical insights in this regard. Thus, it becomes inevitable to explore how and what role the newspaper media in Saudia is playing in the realization of Saudi Vision 2030 particularly the climate revolutions.…”
Section: Literature Reviewmentioning
confidence: 99%